Practical paediatrics - South, M. (Mike); Isaacs, David, 1950- (Elsevier, 2012)
A textbook of paediatrics that describes childhood disease within the context of social determinants of illness, such as genetic origins and social factors. It emphasises on differential diagnosis from a presenting-problem viewpoint, making it suitable for problem-based learning style of curriculum.